Suggestions and Recommendations of Face Mask Usage during COVID 19 Pandemic - Abedin, Nafisa; Bushrah, Kazi Nabila; Md Muktadir, Muhit Reza; Disha, Raisa Abedin; Chakravarty, Saumitra (Bangladesh Journal of Infectious Diseases, 2020)
Rate of spread of SARS-CoV-2 and number of relevant deaths continue to elevate as the time elapses since its first outbreak. With no readily available curative treatment neither any effective vaccine till now to prevent the infection, practicing personal protection measures remain the only effective way to stay protected from its attack. Those who are directly exposed to the care of any confirmed or suspected COVID-19 patient, including the health care workers and caregivers, have been advised by the World Health Organization (WHO) and Centre for Disease Control and Prevention (CDC) to wear proper face masks or respirators following the guidelines. Transmission of corona virus occurs through respiratory droplets, close personal contact as well as touching stuff or surfaces polluted by the viral particles. However, several studies have already proven the effectiveness of using various face masks, according to the circumstances, in preventing the dissemination of COVID-19. Bangladesh Journal of Infectious Diseases 2020;7(1):27-32